Suicide Prevention Audit in Accordance With the NCISH Toolkit – A PAN Trust Audit Across the Four Localities of the Black Country - Rhea Mathews; Sharada Abilash; Jaikishan Athi; Tanika Brandaro; Georgia Smith (BJPsych Open, 2025)
Aims: The primary aim of the re-audit was to identify specific areas where key components of the NCISH guidelines were not consistently applied in the care of patients who died by suicide. By addressing these gaps, the Trust seeks to ensure that NCISH-recommended standards are embedded into practice across all patient care pathways. Our objectives were to assess the level of compliance with NCISH standards across all localities where patients died by suicide, evaluate whether the care provided aligns with National Standards and extract key lessons from the cases audited to drive improvements in care delivery and patient safety.